Neighbourhood watch community portal: Local residential area / Lim Choon Hoe - Lim , Choon Hoe (2003)
-EngAnnWatch- is a web based system that promises quick and efficient ways to strengthen Taman Eng Ann neighbourhood watch. The entire system provides interactive information to build a happy living home for residents. -EngAnnWatch- is another way for residents to communicate while they are busy with their daily duties. The objectives of -EngAnnWatch- are to create a virtual space for Taman Eng Ann to share information for every aspect like ecurity, activities, events, information and so forth. The user interface design is target at non- xpert computer users to widen the scope of users. Rapid Application Development model is used to develop -EngAnnWatch-. The tools involved in the development of -EngAnnWatch- are Macromedia Dreamweaver MX, Microsoft IIS, Adobe Photoshop 7.0, Microsoft office XP Access Database, Word, Visio, Macromedia Flash MX 2004, Microsoft Visual Studio .NET, and .NET framework. It is hope that -EngAnnWatch- will offer more knowledge and information as well as promote the importance of e-neighbourhood watch to the public. Getting to know crime definitions and preventions will make us aware of the damage done to ourselves and our lover at every second of our life. Important information are essential when we facing any emergency situation or disaster. After all, human always seek for new solution especially the way to communicates. This is why-EngAnnWatch- is created; an interactive e-community.